Dieta y patrón reproductivo de Rhogeessa minutilla (Chiroptera: VespertUionidae) en una zona árida de Los Andes de Venezuela - Sosa, Maricela; De Ascencao, Antonio; Soriano, Pascual J (Revista de Biología Tropical, 1996)
The diet and reproductive condition of the bat Rhogeessa minutilla was evaluated throughout a year in a thom shrub of the xerophitic pocket of Lagunillas in the Venezuelan Andes. The analysis of fecal samples showed that this vespertilionid bat eats small insects (3-12 mm) which are represented in 10 orders and 29 families. of the global diet, 84.9% belongs to four orders: Diptera (42.5), Hymenoptera (18.2), Lepidoptera (13.3) and Coleoptera (10.9). The wide range of diet and seasonal replacement of the prey taxa, seem 10 point out that R. minutilla is an opportunistic species in terms of the kind of prey, but selective in its size and hardness. The reproductive data reveals a single peak of pregnancies in the March-May periodo and presence of juveniles in June-July. This seems to indicate a seasonal monoestrous reproduetive pattem probably as a response to the major inseet availability in the rainy season.